An analysis of low and high lexical meanings in a monolingual Arabic dictionary - Alhalawani, Ali Alsayed Hassan (2017)
This study investigated the difference between low and high meanings in a monolingual Arabic dictionary, namely Al-Munjid by (Ma’luf, 1973). As technical terms, low and high meanings were first introduced by (Sanat, 1998). They represent the gap between the ordinary usage of the lexical item, the low meaning, and the implied religious meaning, which is regarded as high. The study examined seven randomly-chosen lexical entries to see whether they cover all possible low and high meanings. Among the objectives of this study were: Firstly, to account for the veracity of the meanings in the given lexical items with respect to their low and high meanings. Secondly, to raise language users’ awareness of the tacit differences in meaning that may exist when religious contexts are considered. A descriptive analytical method was adopted and, hopefully, the outcome would help Arab lexicographers produce dictionaries accommodating low and high meanings that have already become an integral part of competent Arabic speakers’ vocabulary. It would also help draw the attention of Arabic dictionary users to such indispensable high meanings. Preliminary results of the study show that Al-Munjid dictionary tends not to list the high meanings, especially those found in Islamic resources, and instead purposefully focuses only on the low meanings. Based on these results, monolingual Arabic dictionaries are recommended to provide low and high meanings of the lexical entries side by side, as using examples from religious resources can be of major significance in rendering the meanings clearer and more comprehensive. Results and implications of the findings are to be discussed further.